A Gestão nas empresas familiares: um estudo de caso - Gamito, Beatriz Guimarães Ferreira Mendes (2021)
This thesis focuses on the universe of family businesses and all of the components that are part of these, highlighting the importance of this theme in the Portuguese economy. For a better understanding of this theme a brief analysis of what it means to be a family business was carried out, analyzing therefore a number of definitions previously mentioned by different authors who have studied the field. We then move on to the characteristics of family businesses and the impact that each of them has in the companies concerned, then analyzing the pros and the cons. We then reviewed the different types of management controls that exist and which ones are used by companies with this type of genesis, then moving to the dimensions that a management control system hat to contain in a family business. Finally, we analyze the characteristics of management controls in family businesses. The whole literature review has the main function of differentiating a so-called ordinary enterprise from a family business, analyzing all the literature available to date that despite being restrict allowed us to understand the contours of a family business and why this kind of company is so common among Portuguese companies. The literature as well as the existing studies in this area imply that these companies have unique characteristics that result from their composition and that differentiate them from the rest. In this thesis we will evaluate the repercussions that these characteristics have on the management controls and how management plays its role. For a better understanding of the theme we were conducting a case study based on a family business in the area of Furniture and Decoration. This company meets most of the definitions mentioned by the different authors over time about what it is to be a family business, however, and because it is a company with a very small size and only two workers belonging to the family and who are also the managers of the company, some of the consequences of working with family members are not felt. Consequences such as the fact that they not feel the pressure or any kind of rivalry within the business environment, or that there are no problems or dysfunctions caused by the overlap of functions, are unusual points that only happen in the company studied by its reduced constitution and because there is only one employee in the company. This stability and confidence as a couple and the values brought to the company have allowed it not to suffer from some of the most common problems in companies with a large number of family members performing their duties in the family company, thus having a very strong organizational culture. Despite all this, the company studied complies with most of the points highlighted during the literature review, as with most of the family businesses. We conclude that, like most companies with this type of constitution, it predominantly uses informal controls, giving preference to the interpersonal side. The organizational culture in the company is considered strong, and there is a significant link between the company and its founder, and its vision. The fact that there is a common history among family members and a deep knowledge among them are also characteristics that were being perceived in this organization and that are common in this type of companies.